2013
DOI: 10.1093/aob/mct034
|View full text |Cite
|
Sign up to set email alerts
|

Flowering time control in ornamental gloxinia (Sinningia speciosa) by manipulation of miR159 expression

Abstract: miR159-regulated GAMYB expression is an effective pathway of flowering time control in gloxinia. Transgenic manipulation of miR159 can be used as an applicable strategy to regulate flowering time in commercial ornamental plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 33 publications
1
54
1
2
Order By: Relevance
“…However, we do not rule out that other miRNA families also have roles in developmental timing (Li et al, 2013;Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…However, we do not rule out that other miRNA families also have roles in developmental timing (Li et al, 2013;Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…In studies of the molecular mechanisms of tree aging, many age-related genes have been identified (Busov et al 2004;Carlsbecker et al 2004;Diego et al 2004;Fernández-Ocaña et al 2010;García-López et al 2014;Hutchison et al 1990;Li et al 2010Xu et al 2016;Zhang et al 2016), such as miR156 (Wang et al 2011b) and Flowering Locus T (Böhlenius et al 2006;Hsu et al 2006Hsu et al , 2011, and some have been used to change the agronomic traits of plants (Flachowsky et al 2012;Kotoda et al 2006;Li et al 2013a;Yamagishi et al 2014). Larix kaempferi is a forest tree of important ecological and economic value, widely grown in the Northern Hemisphere, but its genome has not been sequenced.…”
Section: Communicated By F Gugerlimentioning
confidence: 99%
“…Experimental studies show that miR 159 directly cleaves mRNAs encoding GAMYB‐related proteins and further controls floral initiate and another development (Achard et al, ; Li et al, ). Transgenic plants with overexpressed miR159 levels significantly delay in floral initiation and flowering under short‐day photoperiods (Achard et al, ; Li et al, ). In contrast, inhibited miRNA expression caused early flowering (Li et al, ).…”
Section: Mirna‐based Biotechnology For Improving Plant Development Fmentioning
confidence: 99%
“…Transgenic plants with overexpressed miR159 levels significantly delay in floral initiation and flowering under short‐day photoperiods (Achard et al, ; Li et al, ). In contrast, inhibited miRNA expression caused early flowering (Li et al, ). miR 172 not only regulate flower development but also involve in floral meristem initiation and phage change; this process is achieved through the interaction of miR 172 and its target Apetala 2 (AP2) that regulates the expression of SOC1, LFY and AP1 (Aukerman and Sakai, ; Chen et al, ; Mlotshwa et al, ; Glazinska et al, ; Zhu et al, ; Wollmann et al, ; Yant et al, ; Zhu and Helliwell, ; Varkonyi‐Gasic et al, ).…”
Section: Mirna‐based Biotechnology For Improving Plant Development Fmentioning
confidence: 99%